Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content:1. The effectiveness of a proposed study unit in economic geography subject in developing knowledge, skills and attitudes of Omani female students at grade eleven towards entrepreneurship in Muscat Governorate in the Sultanate of OmanMrs. Najah Salim Hudeb Al-Habsi2. Extent does the primary school mathematics teachers in Makkah Al-Mukarramah aware of the manifestations of difficulties in learning arithmetic (dyscalculia) among female studentsMrs. Sawsan Ahmed Al-Afifi3. The Effect of a Program based on Gardner's Five Minds Theory on the Development of Undergraduate Mathematics Graduate Students' Creative Thinking at the Faculty of Education- Sana'a UniversityMrs. Eman Ahmed Al-Maqtari , Prof. Radman Mohamad Saeed4. The Hidden Curriculum and its Role in Students' Acquisition of Cultural Values and Behavioral PatternsDr. Hani Ahmad Alkriameen, Dr. Ahmed Odeh Qarareh5. The Status of Using Blended Learning in Teaching the English Language at High Schools from the Teachers’ Point of ViewDr. Amal Mohammad Al-Momani6. The effectiveness of employing 3D interchange graphics in a diffuse learning environment on the science skills of health and life path students in the secondary stageCo-Prof. Khaled Nasser Alqahtani7. The impact of blended learning on students' motivation towards learning and social studies teachers' attitudes towards it in Al-Sharqiyah South Governorate in the Sultanate of OmanMrs. Aisha Abdullah Muhammad Al Majali, Mr. Fahd Salem Saif Al-Masrouri8. Improving English Speaking Skills at Saba UniversityDr. Khaled Mohsen Mohamed Zuheer
Keywords: Journal of Curriculum and Teaching Methodology